Profile Of Liver Enzymes In Non-Alcoholic Fatty Liver Disease: Relation With Type 2 Diabetes Mellitus And Hypertension - Akter , Sheley; Shahidullah, Abul Hasan Md; Akhter, Shahin; Tofazzal, Fatema; Begum, Momtaz (Journal of Chittagong Medical College Teachers' Association, 2026)
Background: Non Alcoholic Fatty Liver Disease (NAFLD) is the most common chronic liver disease worldwide. It is frequently associated with obesity, type 2 Diabetes Mellitus (DM) dyslipidemia and Hypertension (HTN). NAFLD patients may have higher level of serum Alanine Aminotransferase (ALT) serum Aspartate Aminotransferase (AST) or both. The aim of our study was to assess the profile of hepatic enzymes, specially serum ALT and AST in patients with USG-diagnosed NAFLD with regards to presence or absence of DM and HTN. Materials and methods: This cross sectional observational study was conducted in the Department of Physiology, Chittagong Medical College (CMC) during the period of January 2016 to December 2016. Total seventy five subjects, having fatty liver disease on ultrasonography, done by Radiologist of CMCH and fulfilling the inclusion and exclusion criteria were included in the study. Anthropometric measurments and clinical examinations were done. Serum ALT and serum AST level, Fasting Blood Glucose (FBS) and 2 Hrs Post Prandial Blood Glucose (2HPPBS) were estimated according to standard guideline. Data analysis was done by computer based software SPSS windows version 20. Data were expressed in mean ± SD. Students “t” test and chi-square test were done. Results: Liver enzyme ALT and AST were found elevated in 68% and 44% of the NAFLD patients respectively. Mean (± SD) ALT and AST were also higher than normal. Both ALT and AST were significantly higher in older patients with type II diabetes mellitus and hypertension. Only ALT elevation was significantly associated with systolic blood pressure. Conclusion: This study revealed that hepatic enzymes, ALT and AST elevate in NAFLD patients and also highlighted the importance of Type 2 Diabetes mellitus, hypertension to assess everyones risk for NAFLD. So, these enzymes should also be evaluated in NAFLD patients. JCMCTA 2025 ; 36 (2) : 41-45